Triggers and mediators of epigenetic remodeling in plants - Comai, Luca (Frontiers in Epigenetics and Epigenomics, 2023)
Plant epigenetic studies have revealed that developmental or environmental events can trigger both local and global epigenetic remodeling. In multiple cases, transposable elements (TE) respond to the trigger and act as mediators. Epigenetic remodeling results in mitotically and even meiotically persistent states that impact phenotype and could contribute to its plasticity. The challenge is to understand the mechanisms that trigger and mediate remodeling, their evolutionary role, and their potential in breeding.